The differential acoustic diagnosis between two Pseudopaludicola sister species (Anura, Leptodactylidae, Leiuperinae) - Andrade, Felipe Silva De; Haga, Isabelle Aquemi; Bang, Davi Lee; Giaretta, Ariovaldo Antonio (Zootaxa, 2017)
The dwarf swamp frogs, genus Pseudopaludicola, include 21 species, which occur throughout South America (Frost 2016). Pseudopaludicola is recognized as monophyletic, supported by a set of osteological, morphological, and molecular characters (Veiga-Menoncello et al. 2014, and cites therein). Veiga-Menoncello et al. (2014) recognized a clade (“clade II” there), which included two species that share karyotypes with 2n = 20: P. ameghini (Cope, 1887) and P. ternetzi Miranda-Ribeiro, 1937. However, historically these two sister species have undergone many taxonomic changes and so far they do not have a clear taxonomic diagnosis one from the other (Haddad & Cardoso 1987; Lobo 1996; Fávero et al. 2011; Pansonato et al. 2013; Cardozo & Toledo 2013, and cites therein).